2019
DOI: 10.1111/bjep.12266
|View full text |Cite
|
Sign up to set email alerts
|

School‐related subjective well‐being promotes subsequent adaptability, achievement, and positive behavioural conduct

Abstract: Background Previous studies have shown that subjective well‐being and adaptability are linked to adaptive educational outcomes, including higher achievement and lower anxiety. It is not presently clear, however, how school‐related subjective well‐being and adaptability are related, or predict behavioural outcomes such as student conduct. Aim The aim of the present study was to test a bidirectional model of school‐related subjective well‐being and adaptability, and how they relate to achievement and behavioural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 52 publications
(88 reference statements)
5
49
1
7
Order By: Relevance
“…A few studies considered subjective well-being and school achievement, indicating positive associations between the two variables, mostly through cross-sectional designs [27][28][29]. Similar associations were identified also through some longitudinal studies [5,13,[30][31][32].…”
Section: School-related Well-being and Educational Outcomesmentioning
confidence: 68%
See 4 more Smart Citations
“…A few studies considered subjective well-being and school achievement, indicating positive associations between the two variables, mostly through cross-sectional designs [27][28][29]. Similar associations were identified also through some longitudinal studies [5,13,[30][31][32].…”
Section: School-related Well-being and Educational Outcomesmentioning
confidence: 68%
“…Notwithstanding the large number of studies on test anxiety, research focusing on its relation with subjective well-being is scarce [30,33]. The studies which examined the relations between well-being at school and achievement emotions [5,13,32] revealed that school-related well-being was positively associated with pleasant emotions such as enjoyment and pride, while it was negatively associated with unpleasant emotions such as anxiety, anger, shame, boredom, and hopelessness.…”
Section: School-related Well-being and Educational Outcomesmentioning
confidence: 99%
See 3 more Smart Citations